ASSIM NA TERRA COMO NO CÉU: o reflexo da estrutura social nos politeísmos - Tavares, Diego Fontes de Souza (Anais dos Simpósios da ABHR, 2016)
ASSIM NA TERRA COMO NO CÉU: o reflexo da estrutura social nos politeísmos